Recycling of mining tailings into construction materials such as geopolymer cement. (LACCEI, 2024)
Mining is an extractive activity of great importance for the economic development of any country. The Peruvian mining industry is one of the largest in Latin America and contributes to the country's growth by being a crucial source of income. Mining activities generate an increase in the production of waste, which in turn increases environmental pollution and has a negative impact on human health. For this reason, companies must incorporate the Sustainable Development Goals (SDGs) into their operations, consolidating global efforts in favor of environmental sustainability and economic development. The objective of this research is to determine the sustainability of geopolymeric cement production based on laboratory test results carried out on mining tailings in the northern Sierra of Peru. In this way, the pollutant agent (tailings) can be eliminated and a highly useful product (cement) can be generated. Once the chemical and metallurgical analyses of the tailings were completed, the objective was to minimize the presence of toxic elements for humans (heavy metals). After preparing the geopolymeric cement, physical property tests, radiometry analysis, and an economic feasibility study were conducted